Different effects of plasmids harboring blaOXA-232 between major and minor clones in Klebsiella pneumoniae - Yun Young Cho; Hyun Woo Kim; Si Ho Kim; Yu Mi Wi; Kwan Soo Ko (Microbiology Spectrum)
ABSTRACT This study investigated the differing impact of introducing the globally reported blaOXA-232-harboring ColE-type plasmid on the plasmid stability, competitiveness, virulence, and gene expression of Klebsiella pneumoniae transconjugants from major high-risk genotypes (ST11, ST15, and ST307) compared to minor genotypes. Plasmid transformation was performed with electroporation. The carbapenem resistance, plasmid stability, competitive fitness, and virulence were assessed through antibiotic susceptibility profiling, plasmid stability, competition assay, human serum resistance assay, and quantitative real-time PCR. Consistent plasmid stability was evident across all genotypes and nutrient conditions tested following the introduction of the plasmid. K. pneumoniae transconjugants from major clones demonstrated increased competitiveness and virulence compared to their wild-type counterparts, while those from minor clones did not. Increased expression of the virulence-associated fimH gene was observed only in the transconjugants from the major clones. These results highlight a complex interplay between plasmids and bacterial hosts and explain why specific clones producing carbapenemase are frequently observed globally.IMPORTANCEOXA-232 is a variant of OXA-48-like carbapenemase, exhibiting high hydrolytic activity against penicillin and weak activity against carbapenems. It was associated with widespread dissemination of carbapenem-resistant Enterobacteriaceae including Klebsiella pneumoniae. Particularly, it has been identified that high-risk clones (ST11 and ST15) of K. pneumoniae frequently harbor the plasmid with blaOXA-232, that is, ColE-type plasmid. In this study, it is revealed that K. pneumoniae of high-risk clones with ColE-type plasmid harboring blaOXA-232 showed an increase in competitiveness and virulence. It may explain why certain carbapenemase-producing clones are widespread worldwide, emphasizing the need to focus on coping with antibiotic resistance.